2021
DOI: 10.1111/1758-2229.12929
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics of marine microbial communities following a Phaeocystis bloom: biogeography and co‐occurrence patterns

Abstract: Marine microbes play important roles in the development of phytoplankton blooms. The diversity and composition of free living (FL) and particle attached (PA) microbial communities have been well studied, while little is known about their geographic and cooccurrence patterns, especially during the subsiding process of Phaeocystis globosa blooms. Herein, the beta-diversity of FL and PA microbial communities in both the surface and bottom layers of different habitats were comprehensively examined during successio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 66 publications
0
3
2
Order By: Relevance
“…In the present study, dominant bacteria in the intracolonial fluid were completely different from the dominant bacteria observed by Xu et al (2021) during P. globosa blooms, neither in free-living fraction (0.22-3 μm) nor in particle-attached fraction (3-20 μm). However, NS5 marine group, which belongs to Proteobacteria, was observed as one of the dominant bacteria in seawater free-living fractions at the bloom site from both studies.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…In the present study, dominant bacteria in the intracolonial fluid were completely different from the dominant bacteria observed by Xu et al (2021) during P. globosa blooms, neither in free-living fraction (0.22-3 μm) nor in particle-attached fraction (3-20 μm). However, NS5 marine group, which belongs to Proteobacteria, was observed as one of the dominant bacteria in seawater free-living fractions at the bloom site from both studies.…”
Section: Discussioncontrasting
confidence: 95%
“…A number of bacteria in ambient seawater were clearly associated with Phaeocystis, and it was suggested that the bacteria and Phaeocystis established a mutualistic association (Delmont et al, 2014). In the northern Beibu Gulf of China, Xu et al, 2021 demonstrated that microbial communities from P. globosa bloom and non-bloom sites exhibited distinct community composition, and the bloom microbes were likely driven by high environmental selection. However, the microbial community enclosed by the colony envelope is still unknown, and hence the importance of the microenvironment in establishing the unique phytoplanktonbacteria association remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the most dominant bacterial genus, Marinobacter , as identified in this study, was not the most dominant one in previous studies which used P . globosa strains differ from the current study ( Xu et al, 2021a , b ; Zhu et al, 2021 ). These results suggest that different P .…”
Section: Discussioncontrasting
confidence: 91%
“…Plates were then incubated at 20°C for 7 days in the dark. Bacterial colonies exhibiting different morphological characteristics were isolated and stored in marine broth 2216 (MB, BD Difco) supplemented with 20% glycerol to form stocks that were stored at −80°C for future experiments ( Xu et al, 2021a , b ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, nitrogen-fixing bacteria supply inorganic nitrogen to cyanobacteria in exchange for organic exudates ( Yang et al, 2017 ). In another example, the genera Sphingopyxis and Limnobacter (of Proteobacteria ) can degrade microcystins produced by Cyanobacteria ( Yang et al, 2017 ; Xu et al, 2021 ). On a separate note, human-associated pathogenic bacteria were enriched in both the PA and FL fractions in Lake Tianmu, which may pose a health hazard to humans reliant on Lake Tianmu for water ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%